Analisis Jenjang Karir dan Minat Menjadi Perawat Intensif - Eva Metalita; Hanny Handiyani; Tuti Afriani; Lilis Rayatin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to analyze career paths and interest in being an intensive nurse and develop problem-solving solutions by conducting interactive discussion activities to disseminate intensive unit services to attract interest in becoming an intensive nurse. The method used is a case study and analysis of results and implementation gaps with a discussion based on the literature review. The results of the career path analysis research, respondents have a D3 nursing education level (90%), 5-8 years of service (87.5%), occupy the last PK level 1-5 years (93.4%) and attend BHD, PPI training, PCNT, BHL/PALS, and basic KMB training (53.3%). Interest in being an intensive nurse (63.3%). Interest in carrying out their respective roles as caregivers, educators, and researchers (60%). In conclusion, some nurses are interested in becoming intensive nurses with the appropriate level of education, tenure, and career level and have attended basic training to become intensive nurses. However, when internal recruitment is carried out to become intensive nurses, few nurses are willing to become intensive nurses, so that still needs proper implementation. Keywords: Career Path, Interests, Intensive Nurse